2023
DOI: 10.3390/foods12112192
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Classification of Saffron Adulterants by Vis-Nir Imaging, Chemical Analysis, and Soft Computing

Abstract: Saffron (Crocus sativus L.) is the most expensive spice in the world, known for its unique aroma and coloring in the food industry. Hence, its high price is frequently adulterated. In the current study, a variety of soft computing methods, including classifiers (i.e., RBF, MLP, KNN, SVM, SOM, and LVQ), were employed to classify four samples of fake saffron (dyed citrus blossom, safflower, dyed fibers, and mixed stigma with stamens) and three samples of genuine saffron (dried by different methods). RGB and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that competitive advantages based on an organization's internal capabilities are the best source for acquiring competitive advantage. In this context, various definitions have been provided, all of which deal with the concept of competitive advantage to some extent [20,21]. Competitive advantage means the attractiveness of a company's offerings relative to its competitors from the customers' point of view.…”
Section: 1 Sustainable Competitive Advantagementioning
confidence: 99%
“…Recent studies have shown that competitive advantages based on an organization's internal capabilities are the best source for acquiring competitive advantage. In this context, various definitions have been provided, all of which deal with the concept of competitive advantage to some extent [20,21]. Competitive advantage means the attractiveness of a company's offerings relative to its competitors from the customers' point of view.…”
Section: 1 Sustainable Competitive Advantagementioning
confidence: 99%